Removal of heavy metals from wastewater using reverse osmosis - Kapepula, Vercus Lumami; Luis, Patricia (Frontiers in Chemical Engineering, 2024)
This chapter presents an overview and innovations in reverse osmosis membrane pro-cesses for rejecting charged metal ions in wastewater, in relation to the main problems associated with purification methods. It also explains the emergence of nanomaterials and the different methods applied for RO membrane modification to improve perfor-mance. Membrane regeneration and retentate management have been studied in this chapter. Finally, an economic feasibility study is recommended for the industrial scale-up of the methodology.